Tax implications of the proposed repeal and enacted amendment of the foreign employment exemption, section 10(1)(o)(ii) on South African expatriates - Govender, Kirissa (My University, 2019)
The purpose of this report is to discuss how the proposed repeal and enacted amendment of the foreign employment income exemption, section 10(1)(o)(ii) of the Income Tax Act of 1962 (Act 58 of 1962) (‘the Act’), impacts on South African expatriates (expats) and its impact on the economy. As a result of the proposed amendment in the draft Taxation Laws Amendment Bill 2017, a comparison will be done to compare South African expatriates in a country with no income tax, such as the United Arab Emirates (UAE), to a country with income taxes such as Australia. With this comparison, the aim is to also determine if National Treasury’s purpose of the proposed repeal are met. National Treasury’s main purpose for proposing this repeal was to prevent income earned by South Africans not being taxed in jurisdictions where no tax is imposed on income or in jurisdictions with low tax rates. National Treasury also stated that this exemption creates unequal tax treatment between South African residents employed by a national, provisional or local sphere of government, any public or municipal entity or the private sector (National Treasury, 2017b). The proposed repeal may be a solution to prevent unequal tax treatments amongst South African residents, as mentioned above; it may however result in unfair tax consequence amongst South African expatriates in counties with similar or lower tax rates than South Africa. This report will also analyse alternative solutions for these expatriates such as double taxation agreements (‘DTA’) (tax treaties), other exemptions in the Act, such as a section 6quat rebate or deduction in respect of foreign taxes on income and change of tax residency.
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce specializing in the field of taxation, University of the Witwatersrand, Johannesburg, 2019
Keywords: Taxation--Law and legislation--South Africa; Income tax deductions--South Africa; Corporations--Taxation--South Africa